ANALISIS SURVEY TINGKAT KEPUASAN WARGA PUCUNG 1 TERHADAP PEMBUATAN TAMPULAMBOT - galih wulandari subagyo; Rizka Arbaningrum; Resdiansyah Resdiansyah (INDONESIAN JOURNAL OF CONSTRUCTION ENGINEERING AND SUSTAINABLE DEVELOPMENT (CESD), 2021)
This study aims to measure the level of satisfaction of the residents of Pondok Pucung 1 towards community service activities making tabulampot. Data was obtained by distributing questionnaires to 15 respondents who were measured using a Likert scale. The results showed that from nine aspects, namely the delivery of goals and objectives of community service by the implementers of the activity time for village officials, 0.917 were strongly agreed. In delivering the goals and objectives, it is equipped with materials such as power points, etc., from 0.9, which is strongly agree. The suitability between the delivery of goals and objectives with the implementation in the field is 0.967, which is strongly agree. There is a difference between before the community service activities were carried out and before the activities were 0.983, which is strongly agree. The community around the community service location helps for plant care 0.967, which is very agreeable. In general, citizens' satisfaction with the existence of community service activities 1, which is strongly agree. Tabulampot gardens make the environment beautiful 1, which is very agreeable. Tabulampot gardens make local residents more comfortable 0.983, which is very much agree. Tabulampot gardens make local residents more peaceful 0.983, which is very agreeable. Overall, the residents of Pondok Pucung 1 are very satisfied with the community service in making tabulampot.